Measuring Vehicle Emission Loss Costs of Students of the Faculty of Economics and Business, Tadulako University with an Environmental Accounting Approach - Pujianti, Erna; Mustamin, Mustamin; Kahar, Abdul; Jamaluddin, Jamaluddin (Jurnal Samudra Ekonomi dan Bisnis, 2025)
Located in Palu City, Tadulako University is among the biggest emitters of pollution from heavy traffic. Particularly gasoline and diesel motor vehicles, transportation greatly adds to the higher emissions. This study intends to identify the elements influencing vehicle exhaust emissions and transportation activities, build a relationship model between them, compute the emissions amount, and project economic losses resulting from exhaust emissions at the Faculty of Economics and Business, Tadulako University. The results of multiple linear regression analysis on the calculation of emission load estimates and projected loss costs reveals that losses resulting from emissions at the Faculty of Economics and Business Tadulako University exceed IDR 18,668,454 annually.